2016
DOI: 10.1111/desc.12428
|View full text |Cite
|
Sign up to set email alerts
|

Reading skill–fractional anisotropy relationships in visuospatial tracts diverge depending on socioeconomic status

Abstract: Low socioeconomic status (SES) has been repeatedly linked with decreased academic achievement, including lower reading outcomes. Some lower SES children do show skills and scores commensurate with those of their higher SES peers, but whether their abilities stem from the same systems as high SES children or are based on divergent strategies is unknown. We here investigated a potential interactive relationship between SES and real-word reading skill in the white matter in 42 typically developing children. SES w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 67 publications
13
49
0
Order By: Relevance
“…Overall, the findings of a positive association between SES with left and right ILF FA and a negative association with RD are in line with documented SES‐related differences in neural structure and function across development (Hanson et al, ; Jednoróg et al, ; Lawson, Duda, Avants, Wu, & Farah, ; Mackey et al, ; Noble et al, ; Noble et al, ; Raizada & Kishiyama, ). Consistent with the present findings, lower parental SES has been associated with decreased FA in multiple white matter clusters including in the bilateral ILF tract in older children (Gullick et al, ). To our knowledge, no studies to date have directly investigated differences in white matter based on SES in younger kindergarten children.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Overall, the findings of a positive association between SES with left and right ILF FA and a negative association with RD are in line with documented SES‐related differences in neural structure and function across development (Hanson et al, ; Jednoróg et al, ; Lawson, Duda, Avants, Wu, & Farah, ; Mackey et al, ; Noble et al, ; Noble et al, ; Raizada & Kishiyama, ). Consistent with the present findings, lower parental SES has been associated with decreased FA in multiple white matter clusters including in the bilateral ILF tract in older children (Gullick et al, ). To our knowledge, no studies to date have directly investigated differences in white matter based on SES in younger kindergarten children.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies that demonstrated modulatory influences of SES on the brain–reading relationship (Brito, Piccolo, & Noble, ; Gullick et al, ; Noble et al, ; Romeo et al, ), ILF FA in kindergarten was associated with better second‐grade reading outcomes in lower‐SES but not higher‐SES children. The longitudinal nature of the current findings is a notable difference from other studies that only examined the SES × brain association with reading concurrently.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In a recent study where low socioeconomic status was determined by level of parental higher education, Gullick, Demir-Lira, and Booth (2016) found that low SES children demonstrated a positive relationship in the right hemisphere homologues when performing reading comprehension tasks, indicating that these children engage in more visuospatial processing to replace their lack of verbal processing ability. This is due in part to low SES children experiencing less verbal environments as their brain matures.…”
Section: Students In Povertymentioning
confidence: 99%